Edward Hopper’s cinema paintings: film palace nostalgia, usherette’s disillusionment, and bomb threats - Rühse, Viola (2020)
Edward Hopper —who is known for his pictorial compositions reminiscent of film scenes and who inspired many filmmakers— went to the cinema himself very often. He also addressed cinema exteriors and interiors as a topic in some of his works. In the following, three central works on cinemas by Edward Hopper —The Sheridan Theatre (1937), The Circle Theatre (1936), and New York Movie (1939)— whose historical context has not yet been examined in detail will be analysed. With their sophisticated compositions, they are very illustrative of cinema history in particular and American history of the 1930s in general. Hopper draws attention to contemporary urban trouble spots for unrest enhanced by cheapening strategies in the film exhibition business. He also deals with the changed cinema experiences in the 1930s and deconstructs the glamour of the job of the usherette and exposes the alienation of their work.